2014
DOI: 10.1089/jmf.2013.0169
|View full text |Cite
|
Sign up to set email alerts
|

Kre-Celazine® as a Viable Treatment for Juvenile Rheumatoid Arthritis/Juvenile Idiopathic Arthritis — A Pilot Study

Abstract: The purpose of this study was to ascertain whether an oral, non-prescription, nutritional supplement compound composed of a proprietary alkali-buffered creatine monohydrate and cetylated fatty acids mixture (Kre-Celazine(®)) was efficacious in reducing or eliminating refractory pain and inflammation, without untoward effects, in Juvenile Rheumatoid Arthritis (JRA), which is also called Juvenile Idiopathic Arthritis (JIA). JRA/JIA is a patho-physiologically complex, chronic childhood autoimmune inflammatory dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…( p = 0.621, 0.166 respectively) Golini and Jones. 2014 [ 21 ] Total:16 Clinical trial Kre-Celazine nutritional Supplement composed of a proprietary alkali buffered creatine monohydrate and acetylated fatty acids mixture Normal range of motion Decreased ESR and CRP Decreased pain scores Gheita et al 2012 [ 22 ] Total:47 JIA:27 Control:20 Controlled trial Dietary supplements of omega-3 FAs A remarkable improvement in: mean active joint count ( p < 0.001) JADAS-27 ( p < 0.001) CHAQ ( p < 0.001) A significant reduction in the ESR Yarema et al 2018 [ 23 ] Total:68 JIA:53 Control:15 Randomised controlled trial Dietary supplements of omega-3 PUFA Immune status significantly improved:(≤ 0.05) Berntson et al2014 [ 24 ] 1 case study Full nutrition by EEN Improvement in: global assessment of pain (VAS 0–100 mm) CHAQ JADAS 27 Berntson et al2016 [ 24 ] 1 Pilot study Full nutrition by EEN A remarkable Improvement in: number of inflamed joints, morning stiffness, global assessment of pain (VAS 0–100 mm) CHAQ Berntson et al2016 [ 24 ] 7 Exploratory study Full nutrition by EEN An immediate anti-inflammatory effect, as shown by reduction in inflammatory Proteins MCP-2, MCP-3 and MCP-4 (monocyte chemoattractant protein) resulting in clinical improvement in patients with JIA and decreased in levels of JADAS27, CHAQ and pain VAS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( p = 0.621, 0.166 respectively) Golini and Jones. 2014 [ 21 ] Total:16 Clinical trial Kre-Celazine nutritional Supplement composed of a proprietary alkali buffered creatine monohydrate and acetylated fatty acids mixture Normal range of motion Decreased ESR and CRP Decreased pain scores Gheita et al 2012 [ 22 ] Total:47 JIA:27 Control:20 Controlled trial Dietary supplements of omega-3 FAs A remarkable improvement in: mean active joint count ( p < 0.001) JADAS-27 ( p < 0.001) CHAQ ( p < 0.001) A significant reduction in the ESR Yarema et al 2018 [ 23 ] Total:68 JIA:53 Control:15 Randomised controlled trial Dietary supplements of omega-3 PUFA Immune status significantly improved:(≤ 0.05) Berntson et al2014 [ 24 ] 1 case study Full nutrition by EEN Improvement in: global assessment of pain (VAS 0–100 mm) CHAQ JADAS 27 Berntson et al2016 [ 24 ] 1 Pilot study Full nutrition by EEN A remarkable Improvement in: number of inflamed joints, morning stiffness, global assessment of pain (VAS 0–100 mm) CHAQ Berntson et al2016 [ 24 ] 7 Exploratory study Full nutrition by EEN An immediate anti-inflammatory effect, as shown by reduction in inflammatory Proteins MCP-2, MCP-3 and MCP-4 (monocyte chemoattractant protein) resulting in clinical improvement in patients with JIA and decreased in levels of JADAS27, CHAQ and pain VAS …”
Section: Resultsmentioning
confidence: 99%
“…From the randomised trials, one study [ 20 ] had an overall low risk of bias, and two had some concern [ 19 , 23 ], while the remaining trials [ 12 , 21 , 22 ] had an overall high concern. For the cross-sectional studies, overall, four studies had good quality [ 9 , 33 , 36 , 38 ] while others were fair [ 10 , 32 , 34 , 35 , 37 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the randomised trials, one study (17) had an overall low risk of bias and two had some concern (18, 19) while the remaining trials (10,20,21) had an overall high concern. For the cross-sectional studies, overall four studies had good quality (22,23,24,25) while others were fair (1,26,27,28,29,31).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Berntson et al (37,38), in one case and one pilot study with one participant and Golini (20) in a clinical trial study with 16 participants reported that in ammation, pain and disease activity improved after treatment with EEN(37,38) which contains protein and Kre-Celazine nutritional supplement composed of a proprietary alkali buffered, creatine monohydrate and fatty acids mixture (20).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Alkaline buffered supplements have been shown to have an antiproliferative effect in human tumor cells more so than non-buffered supplements [20], and may be effective in the treatment of juvenile arthritis [21]. Extracellular alterations in pH around the immediate cell membrane, especially in neoplastic cell models, have been shown capable of affecting the behavior of cell membrane/surface receptors.…”
Section: Cell Lines and Treatmentmentioning
confidence: 99%